STRUCTURA ȘI DIVERSITATEA COMUNITăȚILOR DE MAMIFERE DIN REZERVAȚIA BIOSFEREI „PRUTUL DE JOS” - Sîtnic, Veaceslav; Caraman, Natalia; Caldari Vladislav (CEP USM, 2024)
The structure and diversity of mammalian communities from the ,,Prutul de Jos” biosphere reserve. The research was carried out in the “Prutul de Jos” Biosphere Reserve based on the materials collected in the area during the years 1995-2022. The intended objective was to study the structure and diversity of mammal communities. Relative density determination methods were used. 29 species of mammals have been identified. 6 species are included in the Red Book of the Republic of Moldova. A decrease in the mammal diversity index was established over the last 30 years from 1.97 to 1.62. The landscape reserve is of particular importance for the conservation of biological diversity.
THE STRUCTURE AND DIVERSITY OF MAMMALIAN COMMUNITIES FROM THE ,,PRUTUL DE JOS” BIOSPHERE RESERVE
Keywords: abundance; adaptation; diversity; ecotone; landscape reserve; rare species